The Influence of Financial Knowledge on Financial Satisfaction with Financial Behavior as a Mediating Variable on Cooperative Employees - Rohmatul Laila; Ayu Lucy Larassaty; Jeziano Rizkita Boyas; Edita Rachma Kamila (International Journal of Economics and Management Research, 2025)
This study analyzes the effect of Financial Knowledge on Financial Satisfaction, with Financial Behavior as a mediating variable among cooperative employees. The results show that Financial Knowledge significantly influences Financial Behavior, but not Financial Satisfaction. Financial Behavior also does not significantly affect Financial Satisfaction, indicating no mediation effect. Findings suggest that economic and psychological factors influence financial satisfaction more than financial literacy or behavior. Therefore, cooperatives should enhance employee financial well-being through better incentives, economic stability, and practical financial management.